Sustainable Built Environment in Kazakhstan: The Way towards Better IAQ † - Uyzbayeva, Aigerim (MDPI, 2018)
The fast economic growth, an expanding population and high standards of living required by people has led to increase not only in the urban energy demand but also strengthened the relation between cities, health and the environment. Kazakhstan is currently one of the dynamically developing countries in its region and is experiencing the stable growth in all sectors of the economy which is highly dependent on traditional energy sources like coal, oil and gas. To reduce the energy demand and consumption by the different industrial sectors, Kazakhstan targets shifting towards the sustainable use of the resources through implementing the low-carbon strategies construction sector as well. Sustainable development is a broad topic that outlines 17 goals and to achieve the sustainability in buildings it is vital to consider the relationship between occupants and their living habitat. This paper shortly provides an overview of the energy efficiency situation in Kazakhstan examines the factors affecting sustainable built environment such as indoor air quality.
Keywords: sustainable buildings; radon in Kazakhstan; indoor air quality; energy efficiency in Kazakhstan